Investigation on thermophysical properties of multi-walled carbon nanotubes enhanced salt hydrate phase change material - Rajamony, R. K.; Mahendran, Samykano; Pandey, A. K.; Babu, S. Ramesh; Noor, M. M.; Devarajan, R.; Paw, J. K. Siaw; Natarajan, S. K. (Universiti Malaysia Pahang, 2023)
Thermal Energy Storage (TES) is a valuable tool for improving the energy efficiency of renewable energy conversion systems. One of the most effective methods for harnessing thermal energy from solar sources is through energy storage using phase change materials (PCMs). However, the thermal performance of PCMs is hindered by their low thermal conductivity. This research focuses on enhancing the thermal performance of salt hydrate PCM using multi-walled carbon nanotubes (MWCNTs) and surfactants. Through experimental investigations, a salt hydrate PCM with varying concentrations of MWCNTs (ranging from 0.1% to 0.9%) was prepared using a two-step technique and their thermophysical properties were thoroughly characterized. Various techniques such as field emission scanning electron microscope, thermal conductivity analyzer, ultraviolet-visible spectrum, thermogravimetric analyzer, and Fourier transform infrared spectroscopy were utilized to study the effect of surfactant on the nanocomposites and examine their morphology, thermal conductivity, optical properties, thermal stability, and chemical stability. The results indicated that the inclusion of MWCNTs with salt hydrate significantly improved the thermal conductivity by 68.09% at a concentration of 0.7 wt %, compared to pure salt hydrate. However, this enhancement in thermal performance was accompanied by a reduction in optical transmittance in the developed nanocomposite PCM. Additionally, the formulated nanocomposite demonstrated excellent thermal and chemical stability up to temperatures as high as 468 °C. As a result, this nanocomposite shows great promise as a potential candidate for solar TES applications, offering favourable characteristics for efficient energy storage from solar sources.